A pedagogia de projetos: gerando engajamento e aprendizagem nas aulas de Língua Portuguesa - Santos, Graziela de Oliveira (Universidade do Vale do Rio dos Sinos, 2018)
Faced with the new paradigms that impose on Education today, when some times our students are not in tune with the pedagogical proposals, we as educators have to respond with a right curriculum to the educational demands from various perspectives. In the search for a better understanding of what is possible to do to respond to these demands, this study was realized from the analysis and discussion of the implementation of a project of Portuguese language and Literature teaching practicum in a public school in the year of 2017, with a with a class of the first grade of high school. The objective of the study was to check if the study with reading in Portuguese language through a project can favor the literacy in mother tongue, the main purpose of the study with language at school, as well as other skills to operate effectively as citizens of this century. This research is qualitative, documentary and ethnographic, and is based on the analysis of data of observation and implementation of the project. The analysis of data allowed us to observe that, during the project, the tasks fulfilled were promoters of the competences of the 21st century, recognized by students in their evaluations, such as group work and communication, besides literacy, concretized in the production of texts for a Literary Fair promoted by the school.
Keywords: Projeto; Leitura.; Letramento; Língua materna; Project; Reading; Literacy; Mother tongue